Estimates of Variability, Heritability and Genetic Advance in Foxtail Millet: GENETIC VARIABILITY IN FOXTAIL MILLET - Dhoot, Rupal (Annals of Arid Zone, 2024)
Foxtail millet (Setaria italica (L.) P. Beauv) known globally as Italian millet, Italian foxtail, German millet, Siberian millet, Foxtail bristle grass is having highest production among all small millets making its sixth most important grown grain. In India it is well known as Kangni (Hindi), Kang (Gujarati), Navane (Kannada), Kaon dana (Bengali), Kavalai, and Tenai (Tamil) and is important crop next to finger millet among the small millets. At present, foxtail millet is cultivated in Andhra Pradesh, Karnataka, Maharashtra, Tamil Nadu, Rajasthan, Madhya Pradesh, Uttar Pradesh and north eastern states of India. Millets are far superior than other cereal crops like rice and wheat nutritionally (Shingane et al., 2016). Protein content in foxtail millet grains ranges from 11.13 to 18.75%, being greater than rice (7%-9%), wheat (11%-14%), and maize (8%-11%) (Hou et al., 2022). Having a comparable nutritional profile to common millet, 4 percent oil, with 7% crude fibre. Mature grain is good source of digestible protein than rice and wheat and also contains beta-arotene, antioxidants, vitamins, calcium, iron, potassium, magnesium, zinc. Contains more vitamins and is source of seven of the eight necessary amino acids that the human body cannot generate (Zhang et al., 2007), grains are also very good source of thiamine, riboflavin and niacin.